Postoperative Elevated Resistive Indices Do Not Predict Hepatic Artery Thrombosis in Extended Criteria Donor Livers - Siskind, Eric J.; Vandermeer, Fauzia; Siskind, Tamar R.; Bruno, David A.; Sultan, Samuel; Alvarez-Casas, Josue; Stafford, Arielle; Lane, Barton; Lamattina, John C.; Barth, Rolf N.; Hanish, Steven I. (International Journal of Angiology, 2017)
Postoperative transplant liver ultrasounds were analyzed in standard criteria donor (SCD), extended criteria donor (ECD), and donation after cardiac death (DCD) liver allografts to determine if elevated resistive indices (RIs) are consistently present and if they are pathological. Postoperative transplant liver ultrasounds were reviewed from 115 consecutive patients. Hepatic arterial RIs were stratified based on the type of donor: DCD, macrosteatosis (>30%), or standard criteria. In all patients with elevated RI, subsequent ultrasounds were reviewed to demonstrate RI normalization. The mean RI for all 115 patients was 0.64, DCD was 0.67, macrosteatosis was 0.81, and SCD was 0.61 (p = 0.033). The RI on subsequent liver ultrasounds for DCD and macrosteatosis normalized without any intervention. There were no incidences of early hepatic artery thrombosis (HAT) observed in the cohort. Hepatic arterial RI in ECDs and DCDs are elevated in the immediate postoperative period but are not predictive of HAT. It represents interparenchymal graft stiffness and overall graft edema rather than an impending technical complication. The results of our study do not support the routine use of anticoagulation or routine investigation with computed tomography angiography for elevated RIs as these findings are self-limiting and normalize over a short period of time. We hope that this information helps guide the clinical management of liver transplant patients from expanded criteria donors.
Keywords: liver transplantation; liver transplant ultrasound; donation after cardiac death; hepatic macrosteatosis; hepatic artery thrombosis; extended criteria donors